Sperm penetration assay and its correlation with semen analysis parameters - Pandey, Laxmi Kant; Pandey, Sulekha; Karkare, Shraddha; Sinha, Ruchi; Gulati, Anil K. (International Journal of Research in Medical Sciences, 2017)
Background: Aim of current study was to determine whether the Sperm Penetration Assay (SPA) can be used as a test to discriminate the infertile male from fertile one. We have also correlated the SPA with semen analysis. Methods: Sperm characteristics namely Semen analysis and the sperm penetration assay were tested in 44 infertile and 10 fertile men. Sperm penetration assay was determined by using zona free hamster eggs. Results: With decreasing spermatozoa concentration in the semen there was significant decrease in percentage penetration of zona free Hamster eggs (p<0.001). There was decrease in Sperm penetration assay with deteriorating progressive sperm motility (p<0.05) and no consistent relationship appeared between the sperm morphology and the Sperm penetration assay (p>0.05). Conclusions: The Sperm penetration assay could discriminate the infertile group from fertile group significantly (p<0.001). The test appeared to be highly reproducible and probably identifies a truly infertile male.